Identificación de la calidad del aire “PM10 y PM 2.5” en la mancomunidad de desechos sólidos del cantón Pujilí, provincia de Cotopaxi, período 2022-2023. - Bryan Ramiro, Tapia Vélez (2023)
Air pollution is a universal problem caused by many natural and artificial factors resulting from human intervention. This research project was conducted with the objective of identifying air quality (PM1O and PM 2.5), proposing environmental measures to mitigate pollution and establishing a database of concentrations in the solid waste community of Pujilí canton located in the province of Cotopaxi, Patoa Grande de Maldonado sector, particulate matter produced by the activities carried out in the facilities. The methodology applied was field monitoring with the E-BAM portable environmental beta instrument, which serves as a pollution concentration meter, measuring the increase or decrease of particles by weight, fixing them on a filter-type membrane over a period of 24 hours for 3 days for each type of particulate material fixed, establishing specific points with the UTM Geo Map software used as a manual GPS and recording their coordinates. By means of the information obtained from the concentrations of particulate matter we elaborated a data base with the intention of giving an approach to the improvement of the quality of the air we breathe, establishing levels of emissions and emphasizing the points where there are higher and lower concentrations. The results obtained were analyzed quantitatively by comparing them, associating them with the established LMPs and the ANOVA statistical method, the level of particulate matter (PM1O and PM 2.5) in the community is different at each sampling point and determines air pollution in suspension present with 255 µg/ 10 m3 for PM10 at 11:00 on July 25 called alert level and with 61 µg/m3 for PM2. 5 at 13:00 on July 25 called moderate level, providing a socio-environmental contribution to the population with real data, the same that help reduce the problems caused by direct exposure which establish the maximum permissible limits set out in the current environmental regulations of Ecuador decreed in the (TULSMA) Book VI, Annex 4 of the Environmental Air Quality Standard.